Kajian Implementasi Pembelajaran Berbasis E-learning dengan Pendekatan Unified Theory of Acceptance and Use of Technology (UTAUT) (Studi Kasus pada SMP Al-Amanah, Kota Tangerang Selatan) - Haryanto Haryanto (Jurnal Khatulistiwa Informatika, 2017)
ABSTRACTElectronic learning (e-learning) is educational process take information technology and communication sistimatically by integrating these components of learning, including the interaction of learning traffic space and time with kualitasi certifiable. E-learning do learning long-range used technology computer, computer network and / or internet or computer standalone. The use of technology expected to improve the will and the learning the students in particular smp students. Peggunaan technology and information system will go well if users accept and implement the technology well. One way to see how far influence the application of learning with pemanfatan e-learning is to use the model theory of acceptance and use of technology ( utaut ). With this model will can be seen how relations behavior in acceptance e-learning by the students dilingkungan smp al trustful south tangerang. Research result obtained a very significant relating to behavior users. It is of course can improve quality and the quality of learning in smp al trustful. And therefore can produce graduates more quality.Keywords: e-Learning, Unified Theory of Acceptance and Use of Technology (UTAUT)